Dispensasi Pengadilan Agama Dalam Perkawinan Di Bawah Umur (Studi Kasus Di Pengadilan Agama Karanganyar) - Asri, Setyaning Novita; , Nuswardhani, S.H, S.U; , Septarina Budiwati, S.H., M.H (2016)
This study aims to determine the consideration of judges in issuing marriage licenses granted for minors, legal consequences and the problems that arise when doing under-age marriage in Karanganyar Religious Court. This research method using descriptive empirical jurisdiction. The types and sources of data consist of secondary data, primary legal materials, secondary and tertiary, while the primary data includes interview. The method of collecting the literature study and interview data was then analyzed by qualitative analysis techniques. The results showed: (1) Consideration of the judge in granting the request of underage marriage on the grounds the child is already pregnant beforehand and other concern of parents over the harmful effects/bad impact if nothing is done underage marriage, (2) The legal consequences after the child conduct of underage marriage that the child was considered an adult and the marriage is lawful, along with their rights and responsibilities as husband and wife, (3) Problems that arise consequences doing under-age marriage is the problem of the poor economy and the emotions are still unstable , due to the lack of preparation so susceptible to divorce.